2023
DOI: 10.3389/fimmu.2023.1071675
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis of N6-methyladenosine reader IGF2BP3 as a promising biomarker in pan-cancer

Abstract: BackgroundInsulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3) has been reported to exhibit an oncogenic effect as an RNA-binding protein (RBP) by promoting tumor cell proliferation, migration and invasion in several tumor types. However, a pan-cancer analysis of IGF2BP3 is not currently available, and the exact roles of IGF2BP3 in prognosis and immunology in cancer patients remain enigmatic. The main aim of this study was to provide visualization of the systemic prognostic landscape of IGF2BP3 in pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 75 publications
(92 reference statements)
1
9
0
Order By: Relevance
“…m6A modification is a common and reversible RNA modification that has an important role in post-transcriptional gene regulation. In recent years, extensive research has been conducted to understand the functional significance of m6A modification and its impact on various biological processes (61)(62)(63). In the present study, a significant correlation was observed between the expression levels of FASTKD1 and two genes, namely YTHDF1 and LRPPRC.…”
Section: Discussionsupporting
confidence: 58%
“…m6A modification is a common and reversible RNA modification that has an important role in post-transcriptional gene regulation. In recent years, extensive research has been conducted to understand the functional significance of m6A modification and its impact on various biological processes (61)(62)(63). In the present study, a significant correlation was observed between the expression levels of FASTKD1 and two genes, namely YTHDF1 and LRPPRC.…”
Section: Discussionsupporting
confidence: 58%
“…The fate of m6A‐modified mRNA is determined through proteins that specifically associate with the m6A modification, also known as m6A reader proteins. The first identified and most well studied m6A readers are YTH domain‐containing family of proteins (Chen et al, 2023; Patil et al, 2018; Shao et al, 2021). Over the years YTH domain‐containing proteins have been assigned molecular functions in controlling decay and/or translation of m6A‐modified transcripts.…”
Section: Yth Domain Containing Protein Mrb1/pho92 Is a Conserved Read...mentioning
confidence: 99%
“…IGF2BP1/2/3 is non-canonical readers, for which RNA binding depends not only on m6A modification domain but also on other RNA domains. Readers regulate RNA stability, translation, degradation, and splicing [3, 4].…”
Section: N6-methyladenosine (M6a) and Related Proteinsmentioning
confidence: 99%